Modeling edge-snow interactions using machining theory - Brown, C. A. (Science and Skiing IV, 2009)
INTRODUCTION Merchant's model (1945) for chip formation in machining is applied to the interaction of an edged ski with the surface of snow. Forces for turning while skiing are generated by this interaction, and these forces depend on the shear strength of the snow, the depth of penetration, and the shear angle in the snow. Previously, Leiu and Mote (1985) and Brown and Outwater (1989) have applied cutting experiments and models to edge ice and snow interactions in order to model turning skis and to determine the properties relating to ski-ability of snow.